"Evidence-based medical nutrition – A difficult journey, but worth the effort!". Issue 10 (October 2020) - Kaegi-Braun, Nina; Baumgartner, Annic; Gomes, Filomena; Stanga, Zeno; Deutz, Nicolaas E.; Schuetz, Philipp
Summary: Evidence-based medicine is the art of combining "best external evidence", "clinical judgement" and "patient values" for improved daily clinical decision making and is the ultimate goal in modern medicine. Historically, in the field of medical nutrition, there had been a lack of strong evidence from large and high-quality trials resulting in often weak guideline recommendations and therefore insufficient implementation in clinical practice. Particularly in the field of malnutrition, the medical community has long struggled to find evidence-based approaches for effective management by means of screening, assessment and treatment of patients. With recent trials showing that individual medical nutrition therapy has strong effects on clinical outcomes, we should now aim to practice "evidence-based medical nutrition" (EBMN) by combining clinical judgement (e.g., thorough clinical assessment of the malnourished patient), patient preferences (e.g., integration of perspectives of patients and relatives, consideration of comorbidities to define specific energy/protein goals and appropriate route of medical nutrition therapy) and the most current scientific evidence (e.g., trial-supported use of nutritional interventions for individual patients). Such an approach may certainly be helpful to improve clinical outcomes of the vulnerable population of malnourished medical inpatients.